The appeal of 7de Laan - Nadia van der Merwe (Communicare)
What is described as ‘a major leap of faith’ by producer Danie Odendaal (Labuschagne, 2010: 62) has turned out to be somewhat of a cultural phenomenon. For one, 7de Laan was, at the time of the study, the most popular Afrikaans soap in that it reached a bigger audience than any other Afrikaans soap, such as Binneland2 (M-Net and KykNET)3 and Villa Rosa (kykNET) (TVSA, 2010). It further held its own in the fiercely competitive timeslot of 18:30 during which two other soaps, namely Isidingo (SABC 3)4 and Rhythm City (e.tv), were then broadcast. The soap has also received the Voters’ Choice Award for best soap opera two years’ running at the South African Film and Television Awards, thereby confirming its popularity. Although initially commissioned for the upper-income category (De Lange, 2007: 3), 7de Laan now has a much wider audience base, which includes viewers from different socio-economic, racial and language groups. Using reception analysis as point of departure, this study used in-depth interviews with a cross-cultural sample of viewers to describe the appeal of 7de Laan.